VIKOR AND TOPSIS APPLICATIONS FOR PERSONNEL SELECTION - BİRCAN, Hüdaverdi and DEMİR, Gülay and DÜNDAR, Sinan (Atlas Journal, 2020)
Decision making is a form of behavior used in all areas of life. There are situations such as facilitating daily life for individuals, maintaining their existence and providing the most profit for businesses, and making decisions for countries to compare with other countries. There are criteria that help the decisions taken for all these situations. Especially in the enterprises, while making their decisions, they are faced with choosing the most suitable one among the alternatives available. The presence of complexity of evaluations and ambiguities in reaching ideal solutions for preference of human resources emerges as the most important obstacle in front of the decision making processes for managers as in all matters. From this point of view, the application of the Multiple Criteria Decision Making methods allows for the optimization of such complexities and ambiguities to be minimized. In this study, the most suitable candidate was selected for the position of General Manager to be employed in Sivas Business Development Center, which is carried out by the Central Anatolian Development Agency as a project within the scope of the European Union Pre-Accession Assistance Tool. In evaluations, VIKOR method, which allows sorting and selection between alternatives where there are contradictory criteria, and TOPSIS method, which allows comparison of the proximity and distance of alternatives to the ideal solution, were used. The aim of the study is to measure the success of 2 alternative methods used in personnel selection. According to the VIKOR method process steps, the alternatives given with the abbreviations GM005 and GM103 are evaluated as equivalent and ranked first in the ranking. According to the TOPSIS method, GM103 is the candidate for the general manager who ranks first. Of these two alternative methods, TOPSIS offers only one candidate, while VIKOR offers two. It can be said that the TOPSIS method that proposes a single candidate is more successful in the selection of personnel. With reference to the ranking obtained from the methods applied, the most suitable general manager candidates are presented as suggestions to the board of the company.